Paving Pathways Toward Long‐Life Graphite/LiNi0.5Mn1.5O4 Full Cells: Electrochemical and Interphasial Points of View. (29th June 2022) - Cui, Zehao; Zou, Feng; Celio, Hugo; Manthiram, Arumugam
Abstract: The high‐voltage spinel cathode LiNi0.5 Mn1.5 O4 (LNMO) with no cobalt and low nickel content is promising for lithium‐ion batteries due to its high energy and power densities, good thermal stability, and low cost. However, its high operating voltage (≈4.7 V) results in a decomposition of the electrolyte, severe chemical crossover, and deterioration of electrode‐electrolyte interphases (EEIs), hindering its practical viability. It is demonstrated here that by electrochemically pre‐cycling the graphite in an electrolyte containing 30 wt.% fluoroethylene carbonate, a robust LiF‐rich artificial solid electrolyte interphase can be constructed for surface protection; on the other hand, an electrochemical pre‐lithiation of Fe‐doped LNMO serves as a lithium source for graphite at a full‐cell voltage of 2.6 V. As a result, the full cells with the as‐modified electrodes deliver a high capacity of 129 mA h g −1 with an excellent capacity retention of 93% after 200 cycles, vastly outperforming the full cells with fresh electrodes (120 mA h g −1 initial capacity with 78% retention). Finally, pathways toward long‐life graphite||LNMO full cells are pictured based on the inspirations from the electrochemical modifications and in‐depth analyses of the EEIs in this study. Abstract : Benefiting from the electrochemical modifications on graphite anode and a Fe‐doped LiNi0.476 Mn1.475 Fe0.049 O4 (Fe‐LNMO) cathode, the cycle stability and rate capability of high‐mass‐loading graphite||Fe‐LNMO full cells are greatly improved due to a thin, robust solid electrolyte interphase on graphite, an active lithium reservoir, and good cathode passivation.